PATIENT‐REPORTED OUTCOMES OF QUALITY OF LIFE, FUNCTIONING, AND DEPRESSIVE SYMPTOM SEVERITY IN MAJOR DEPRESSIVE DISORDER COMORBID WITH PANIC DISORDER BEFORE AND AFTER SSRI TREATMENT IN THE STAR*D TRIAL. Issue 8 (16th July 2013) - IsHak, Waguih William; Mirocha, James; Christensen, Scott; Wu, Fan; Kwock, Richard; Behjat, Joseph; Pi, Sarah; Akopyan, Araks; Peselow, Eric D.; Cohen, Robert M.; Elashoff, David
<x xml:space="preserve">Abstract</x> Background Panic disorder (PD) is highly comorbid with major depressive disorder (MDD) with potential impact on patient‐reported outcomes of quality of life (QOL), functioning, and depressive symptom severity. Methods Using data from the sequenced treatment alternatives to relieve depression (STAR*D) trial, we compared entry and post‐SSRI‐treatment QOL, functioning, and depressive symptom severity scores in MDD patients with comorbid PD (MDD+PD) to MDD patients without PD (MDDnoPD). We also compared pre‐ and posttreatment proportions of patients with severe impairments in quality of life and functioning. Results MDD+PD patients experienced significantly lower QOL and functioning and more severe depressive symptoms than MDDnoPD patients at entry. Following treatment with citalopram, both groups showed significant improvements, however, nearly 30–60% of patients still suffered from severe quality of life and functioning impairments. MDD+PD patients exited with lower QOL and functioning than MDDnoPD patients, a difference that became statistically insignificant after adjusting for baseline measures of depressive symptom severity, functioning, and QOL, comorbid anxiety disorders (PTSD, GAD, social, and specific phobias), age, and college education. Conclusions Functional outcomes using QOL and functioning measures should be utilized in treating and researching MDD so that shortfalls in traditional treatment can be identified and additional interventions can be designed to address severe baseline QOL and functioning deficits in MDD comorbid with PD.